Evolutionary pshychology, human mating strategies and the sexually trasmitted diseases - Gilberto N. Ottoni de Brito (DST, 1997)
The presenc essay examines the probable impact of human mating scracegies on the incidenceand prevalence of rhe sexually Transmitred cliseases (STDs) in light of recent hypolherical developmencs in the evolurion of such scrategies in our species (Homo sapiens sapiens). The ideas offered by the audior are based on the revolulion engendered by Darwin's conceptual insights on na rural sclection, and more importanc for the presem essay, sexual selection. It is hosped that a more biological view of human macing strategies (and, by excension, of love) will broaden in perspectives oí the epidemiolgy the STDs. Addirionally, it is hoped that chís view will place nonmedical (behavioral) interventions such as marital (couple) counselling in cases of STDs on firm biological grounds. Furthermore, a strictly biological view is consisrent wich die limited success of sexual education in the prevenrion of these cliseases.